Power, Inequality and the Limits of Climate Reform: Rethinking South Africa’s Just Transition - Olver Crispian (University of the Witwatersrand, Johannesburg, 2026)
South Africa’s climate transition is a paradoxical story: a period of increasingly progressive climate policy and inclusive institution-building between 2010 and 2022 — anchored in the PCC, the Just Transition Framework and the JETP — followed by political pushback, retrenchment and the emergence of a lower-ambition equilibrium. This paper asks why an apparent consensus on a just transition has not (at least yet) consolidated into a permanent settlement, and what this reveals about the relationship between institutions, power and equity (both procedural and distributional). Drawing on Political Settlements Theory (PST), the analysis argues that for climate and just-transition reforms to endure, the distribution of costs and benefits must broadly align with prevailing configurations of power. South Africa’s early momentum was driven by underlying shifts in incentives – climate risks, falling clean energy costs, carbon pricing and concessional finance – affecting the holding power of social partners. But the deeper structure of the post-apartheid settlement, rooted in the minerals-energy complex and rent-distribution networks, remained largely intact, allowing incumbents to reassert themselves as the distributional implications of decarbonisation became clearer. Elite fragmentation, state incoherence and lack of trust resulted in just transition provisions being implemented slowly if all at all, while consensus on a just transition gave way to a more cautious, investment-centred trajectory. The paper traces this arc across four phases: the emergence of a socially negotiated climate consensus (2010 — 2018); a period of ambitious climate policy and institution building (2018 — 2022); the contestation and fragmentation that followed (2022 — 2025); and the consolidation of a lower-ambition equilibrium that reflects more closely the underlying balance of power (2025-). NB: some of these phases overlap, but they are a useful schema for explaining macro-trends. The analysis demonstrates that inclusive policy design and participatory processes alone are insufficient to drive change: implementation depends on the organisational strength of actors able to both support and contest the trajectory of change, and on state coherence and capability to implement it. Technological change, market forces, organisational power and institutional innovation can disrupt incumbent interests and engender new economic sectors and constituencies, highlighting that political settlements are definitely not static. Institutions like the PCC can expand the social foundation of the settlement by enabling emerging actors – clean tech enterprises, unions in new economic sectors, municipalities, community initiatives — to organise, voice demands and gradually increase their holding power. The Just Transition Framework (2022) sketched the architecture of a more equitable settlement; the challenge is to translate this vision into practice backed by the intent and capability to do so. The central question this leaves the reader with is, therefore, not whether a just transition is technically feasible, but what political economy conditions are required to realise it i.e. how changing economic incentives and political 5 institutions can be harnessed to build constituencies capable of shifting the political settlement toward one that is genuinely inclusive, developmental and aligned with a low-carbon climate-resilient future.
Keywords: Transition; Power; Inequality; Climate reform; South Africa; SDG-10: Reduced inequalities; SDG-16: Peace, justice and strong institutions